Caracterização genética de populações de Caryocar brasiliense Cambess. e Jatropha curcas L., espécies potenciais na produção de biodiesel - Alves, Patrícia Ferreira [UNESP] (2013)
The oil crisis in decades, coupled with the need for development of the economies and the consequent increase in demand for fuel and the growing concern for the environment, has revitalized the search for alternative energy sources in Brazil and worldwide. In Chapter I Pequi (Caryocar brasiliense Camb.) Is presented, is a species of which oils to produce biodiesel, produced from vegetable oils, can be extracted became more widely discussed source, however due to the advancement of the frontiers farm, the remnants of this species, symbol of the Cerrado, is in extinct in many regions of Brazil. Given this, the objectives of this study were to investigate microsatellite markers for the playback system in samples of open-pollinated progenies of two populations of C. brasiliense, one located within a stand of eucalyptus (POP-TE) and another in a fragment forest which is the legal (POP-RL) Reserve, Treasury Curucaca, targeting the genetic improvement of this species that can be used to produce biodiesel. Thus, in general, the results show that spatial isolation of the fragment cool reservation of individual trees inside the stand Eucalyptus inbreeding can increase in future generations. In Chapter II, we present the jatropha (Jatropha curcas L.), which is highlighted in the National Program for Production and Use of Biodiesel created by the Brazilian government. The jatropha has high content and quality of this oil in its seeds for biodiesel production. However, little information is available regarding the genetic basis and the cultivation of J. curcas. Thus, the work presented is to evaluate, using microsatellite markers, genetic diversity and the mating system in a population of J. curcas, which form a base population, which can provide support for a genetic improvement program, this species, in the pocket-South Mato Grosso region. Thus, the presence of genetic diversity and the high rate of unrelated individuals, despite high rates of ...